2006
DOI: 10.1007/s00276-006-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

A supraomohyoidal plexus block designed to avoid complications

Abstract: Interscalene blocks of the brachial plexus are used for surgery of the shoulder and are frequently associated with complications such as temporary phrenic block, Horner syndrome or hematoma. To minimize the risk of these complications, we developed an approach that avoids medially directed needle advancement and favors spread to lateral regions only: the supraomohyoidal block. We tested this procedure in 11 cadavers fixed by Thiel's method. The insertion site is at the lateral margin of the sternocleidomastoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
(47 reference statements)
0
11
0
3
Order By: Relevance
“…Studies have been done on a supraomohyoid plexus block to avoid complications or collateral effects on other nerves (Feigl et al, 2006) and the spread of local anesthetic to block peripheral nerves (Munirama et al, 2012). For their part, Feigl et al (2013b), identified a simple orientation mark to carry out the vertical obturator nerve block.…”
Section: Authorsmentioning
confidence: 99%
“…Studies have been done on a supraomohyoid plexus block to avoid complications or collateral effects on other nerves (Feigl et al, 2006) and the spread of local anesthetic to block peripheral nerves (Munirama et al, 2012). For their part, Feigl et al (2013b), identified a simple orientation mark to carry out the vertical obturator nerve block.…”
Section: Authorsmentioning
confidence: 99%
“…The symptoms from these complications might be associated with psychological factors to the vasovagal reflex reaction. Feigl et al [53] demonstrated in their cadaveric study that the group of interscalene blocks by the Winnie technique, with the use of 30 ml, showed spread in a lateral direction in all cases and the dye additionally distributed medial to the anterior scalene and disseminated ventrally and dorsally to the anterior scalene muscle. It reached the phrenic nerve, the vagus nerve, the sympathetic trunk, and the great vessels of the superior mediastinum.…”
Section: New Contributing Factors For Hbesmentioning
confidence: 99%
“…Therefore, the phrenic nerve, stellate ganglion, laryngeal nerve and the vertebral artery were not exposed to the injected solution. Whereas in the cadavers group received an interscalene block by the Winnie technique, the dye spreaded medially to the anterior scalene muscle and reached the phrenic nerve, the vagus nerve and the sympathetic trunk [15]. Urmey et al [6] showed that 100% of the patients with an interscalene brachial plexus anesthesia by the Winnie technique developed ipsilateral hemidiaphragmatic paresis detected by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%